Classroom Management Strategies to Create an Active and Enjoyable Learning Atmosphere for Teachers and Students - Wildan Solihin; Euis Latipah; M Nawal Hotami; M Rizki Maulana (Penerbit Hellow Pustaka, 2025)
Classroom management is a crucial aspect of the learning process, as a well-organized and enjoyable classroom environment can enhance students’ participation and concentration. This article discusses various classroom management strategies that can create an active and engaging learning atmosphere. Through communicative approaches, the use of diverse teaching methods, and the reinforcement of positive discipline, teachers are able to build a conducive classroom climate. This study is expected to serve as a practical reference for prospective teachers during Microteaching or Field Teaching Practice (PPL).